Digital Accounting System Adoption Using Big Data, Cloud, TOE Framework - Arif Rahman Hasdik; Mukarramah Syukur; Dwi Ayu Siti Hartina H; Nurul Huda Yus’an (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This research investigates the factors influencing the adoption of Big Data and Cloud Computing–based Digital Accounting Information Systems (AIS) by applying the Technology–Organization–Environment (TOE) framework. The study adopts a quantitative research design and utilizes Partial Least Squares–Structural Equation Modeling (PLS-SEM) as the primary analytical technique. Data were obtained from 168 respondents, including accounting personnel, finance managers, and internal auditors working in organizations that have implemented or are currently transitioning toward digital AIS. The empirical findings reveal that technological, organizational, and environmental contexts significantly influence the adoption of digital AIS. The structural model demonstrates substantial explanatory capability, with the TOE variables accounting for approximately 67% of the variance in digital AIS adoption (R² = 0.67). Among the examined factors, the organizational context exerts the strongest impact, emphasizing the importance of managerial support, internal readiness, and organizational capability in facilitating digital accounting transformation. Overall, this study enriches the literature on information system adoption, particularly within the accounting domain, and offers practical insights for organizations seeking to enhance the effectiveness of digital accounting system implementation.